Causal Effect of Plasminogen Activator Inhibitor Type 1 on Coronary Heart Disease. Issue 6 (June 2017) - Song, Ci; Burgess, Stephen; Eicher, John D.; ,; ,; ,; O'Donnell, Christopher J.; Johnson, Andrew D.
Abstract : Background: Plasminogen activator inhibitor type 1 (PAI‐1) plays an essential role in the fibrinolysis system and thrombosis. Population studies have reported that blood PAI‐1 levels are associated with increased risk of coronary heart disease (CHD). However, it is unclear whether the association reflects a causal influence of PAI‐1 on CHD risk. Methods and Results: To evaluate the association between PAI‐1 and CHD, we applied a 3‐step strategy. First, we investigated the observational association between PAI‐1 and CHD incidence using a systematic review based on a literature search for PAI‐1 and CHD studies. Second, we explored the causal association between PAI‐1 and CHD using a Mendelian randomization approach using summary statistics from large genome‐wide association studies. Finally, we explored the causal effect of PAI‐1 on cardiovascular risk factors including metabolic and subclinical atherosclerosis measures. In the systematic meta‐analysis, the highest quantile of blood PAI‐1 level was associated with higher CHD risk comparing with the lowest quantile (odds ratio=2.17; 95% CI: 1.53, 3.07) in an age‐ and sex‐adjusted model. The effect size was reduced in studies using a multivariable‐adjusted model (odds ratio=1.46; 95% CI: 1.13, 1.88). The Mendelian randomization analyses suggested a causal effect of increased PAI‐1 level on CHD risk (odds ratio=1.22 per unit increase of log‐transformed PAI‐1; 95% CI: 1.01, 1.47). In addition, we also detected a causal effect of PAI‐1 on elevating blood glucose and high‐density lipoprotein cholesterol. Conclusions: Our study indicates a causal effect of elevated PAI‐1 level on CHD risk, which may be mediated by glucose dysfunction.